2011
DOI: 10.1007/s13105-011-0138-7
|View full text |Cite
|
Sign up to set email alerts
|

Aging-induced alterations in female rat colon smooth muscle: the protective effects of hormonal therapy

Abstract: Aging is associated to oxidative damage and alterations in inflammatory and apoptotic pathways. Aging impairs secretion of several hormones, including melatonin and estrogens. However, the mechanisms involved in aging of smooth muscle are poorly known. We have studied the changes induced by aging in the colonic smooth muscle layer of female rats and the protective effect of hormonal therapy. We used young, aged, and ovariectomized aged female rats. Two groups of ovariectomized rats (22 months old) were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Some data suggest that the origin of these functional changes could be the impairment of the Ca 2+ signals and other intracellular routes controlling the contractile proteins [reviewed in ]. In addition, the mitochondrial potential was altered in colonic smooth muscle cells from aged rat , and we have shown changes in the oxidative and apoptotic parameters of aged rat colonic muscle . These changes were inhibited by melatonin.…”
Section: Introductionmentioning
confidence: 69%
“…Some data suggest that the origin of these functional changes could be the impairment of the Ca 2+ signals and other intracellular routes controlling the contractile proteins [reviewed in ]. In addition, the mitochondrial potential was altered in colonic smooth muscle cells from aged rat , and we have shown changes in the oxidative and apoptotic parameters of aged rat colonic muscle . These changes were inhibited by melatonin.…”
Section: Introductionmentioning
confidence: 69%
“…This manifests in a shift towards oxidative mechanisms and a decline in the efficiency of the proteasome, thus the aging organism will be less resistant to stress conditions and to several diseases [30]. It is demonstrated that the aging process affects the GI tract, which is supported by the following signs and symptoms: delayed transit time, constipation, neuronal loss, and general low-grade chronic inflammation, but the underlying mechanisms are not well elucidated [31,32]. It is well-known that due to the presence of different gonadal hormones, there are predisposition differences between males and females in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…26 MEL treatment can also reverse age-related increases in mucosal 5-HT availability 27 and markers of inflammation in mouse colon. 28 Taken together, these studies suggest that MEL may be antiaging both at the organismal level and also at the level of individual tissues. Therefore, understanding the changes in MEL levels with age may provide insight into the decline in colonic function.…”
mentioning
confidence: 87%